Do Chinese preschoolers follow adults’ suggestions? The impact of suggestion fairness and advisor familiarity on preschoolers’ sharing behavior - Chen, Chang; Zha, Zihan; He, Ru; Zhou, Ying; Zhang, Wenjie (Frontiers in Psychology, 2025)
IntroductionWhile preschoolers’ sharing behavior is an important indicator of social development, it remains unclear how adult suggestions influence their sharing decisions.MethodsThis study investigated how suggestion fairness (fair/unfair) and advisor familiarity (familiar/unfamiliar) affect preschoolers’ sharing behavior and its relationship with emotional experiences. Two experiments were conducted with 187 preschoolers aged 3-6 years (Experiment 1: n = 124, M = 4.54 years, SD = 1.02; Experiment 2: n = 63, M = 5.50 years, SD = 0.28) using a dictator game paradigm.ResultsResults revealed that despite having a more mature understanding of fairness, 5-6-year-olds were more susceptible to adult suggestions compared to 3-4-year-olds. Older preschoolers were more likely to follow suggestions from familiar advisors while showing less compliance with unfamiliar advisors’ suggestions. Additionally, 5-6-year-olds demonstrated greater consistency between fairness judgments and actual sharing behavior, whereas 3-4-year-olds showed a larger cognition-behavior gap. Notably, children who shared more than they deemed fair (“over-sharing”) reported experiencing more positive emotions.DiscussionThis study found that both suggestion fairness and advisor familiarity significantly influence preschoolers’ sharing decisions, with age-specific patterns in suggestion compliance and emotional experiences.